Volleyball Tournaments as a Medium for Strengthening Community Social Cohesion: A Qualitative Community Service Study in Sialang Sakti Village - Ira Firna; Maria Herlinda Dos Santos; Andi Ogo Darmianto; Andi Hajar (Bulletin of Pedagogical Research, 2025)
Social engagement in rural communities continues to face challenges in building solidarity, cooperation, and active citizen participation. This study aims to analyze the role of volleyball tournaments as a medium for strengthening community social cohesion within community service activities in Sialang Sakti Village. The research employed a qualitative approach with a case study design, utilizing participatory observation, in-depth interviews, and documentation techniques. The findings indicate that volleyball tournaments are able to enhance social interaction, strengthen togetherness, and instill values of cooperation, discipline, sportsmanship, and social responsibility. However, several limitations were identified, including variations in participation levels among different age groups and the lack of program sustainability. These findings confirm that community sports function not only as recreational activities but also as important instruments for building social networks and internalizing collective values. Active community participation through such activities can serve as strategic social capital for sustainable village development. Therefore, the development of a more structured and sustainable sports-based community service model is necessary to strengthen long-term social impacts and ensure equitable involvement of all community groups.